Reducing Greenhouse Gas Emissions in Beef Cattle Farming through the Implementation of Animal Welfare Principles, as Part of Sustainable Rural Area Development - Encep Saefullah; Kenedi Kenedi; Dedy Khaerudin (Jurnal Penelitian Pendidikan IPA, 2024)
The beef cattle farming industry is facing a dual challenge - the need to reduce greenhouse gas emissions to combat climate change and the imperative to enhance the daily weight gain of cattle to meet growing global demand for meat. The integration of animal welfare principles stands out as a crucial and multifaceted solution that not only mitigates greenhouse gas emissions but also improves the daily weight gain of beef cattle. The results of this study indicate that the implementation of animal welfare guidelines plays a pivotal role in reducing greenhouse gas emissions. By providing cattle with appropriate nutrition, minimizing stress, and ensuring a healthy and stress-free environment, the emission of methane, a potent greenhouse gas, can be significantly lowered. This approach is not just ecologically responsible; it is essential for meeting international climate commitments and preserving the health of the planet's ecosystems. In addition to its environmental benefits, the integration of animal welfare practices has a profound economic impact. Healthy and content cattle are more likely to exhibit efficient digestion and increased feed utilization, leading to higher daily weight gains. This directly improves the productivity and profitability of beef cattle farming operations. Furthermore, the production of higher-quality meat from well-cared-for animals can drive market demand and revenue, strengthening the industry's economic viability.